2018
DOI: 10.1152/ajprenal.00582.2017
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine disruptor bisphenol A is implicated in urinary voiding dysfunction in male mice

Abstract: Estrogens, acting synergistically with androgens, are known from animal experiments to be important in lower urinary tract symptoms (LUTS) and benign prostate enlargement. Human exposure to environmental estrogens occurs throughout the lifespan, but the urologic health risks in men are largely unknown. Bisphenol-A (BPA) is an endocrine disruptor implicated in male urogenital malformations. Given the role of estrogens in male LUTS, we studied the effects of BPA administered in combination with testosterone (T) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Adult exposure to T + E 2 induced obstructive voiding disorder, associated with droplet voiding pattern and an inability to exhibit sustained voids, bladder hypertrophy, diverticula, calculi, and eventual decompensation with hydronephrosis [60]. Administration of BPA and testosterone (BPA + T) produces similar results in adult male mice [50]. Taken together, these findings suggest that the male urogenital system is subject to disruption by estrogenic chemicals, including BPA, during both fetal and adult life.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Adult exposure to T + E 2 induced obstructive voiding disorder, associated with droplet voiding pattern and an inability to exhibit sustained voids, bladder hypertrophy, diverticula, calculi, and eventual decompensation with hydronephrosis [60]. Administration of BPA and testosterone (BPA + T) produces similar results in adult male mice [50]. Taken together, these findings suggest that the male urogenital system is subject to disruption by estrogenic chemicals, including BPA, during both fetal and adult life.…”
Section: Introductionmentioning
confidence: 85%
“…The vom Saal and Ricke labs have demonstrated that low BPA doses alter the testes, epididymis, seminal vesicles, preputial glands, and prostate in male mice [ [48] , [49] , [50] ]. We have also found statistically significant effects of endogenous and exogenous estrogens on the urogenital sinus (UGS) of fetal mice and rats [ 48 , [51] , [52] , [53] , [54] , [55] ].…”
Section: Frederick S Vom Saal and William A Ricke: Bpa Effects On Tmentioning
confidence: 99%
“…The hypothesis that environmental factors contribute to the high rate of bladder dysfunction in ASD is strengthened by evidence that various environmental chemicals have been shown to alter urinary function in preclinical models [236][237][238]. For example, the estrogenic chemical bisphenol A has been linked to abnormal lower urinary tract function [236,239]. Several PCBs have been identified to have estrogenic activity [96], but whether they alter urinary function is unknown.…”
Section: A Role For Pcbs In Asd Comorbidities?mentioning
confidence: 99%
“…In contrast, the present knowledge about the possible influence of BPA on the urinary bladder is extremely scarce. Although previous studies have noted that exposure to BPA may result in urinary voiding dysfunction 20 and contribute to inflammation and neoplasms 21 , there is not yet any data on the influence of this endocrine disruptor on the nervous structures in the wall of the urinary bladder.…”
Section: Introductionmentioning
confidence: 99%